Is All Communicating Hydrocephalus Really Communicating? Prospective Study on the Value of 3D-Constructive Interference in Steady State Sequence at 3T - (:unkn) unknown (AMER SOC NEURORADIOLOGY, 2009)
BACKGROUND AND PURPOSE: 3D-constructive interference in steady state (3D-CISS) sequence has been used to assess the CSF pathways. The aim of this study was to investigate the additive value of 3D-CISS compared with conventional sequences in the diagnosis of obstructive membranes in hydrocephalus. MATERIALS AND METHODS: A total of 134 patients with hydrocephalus underwent MR imaging examination with a 3T unit consisting of turbo spin-echo, 3D-CISS, and cine phase-contrast (cine PC) sequences. 3D-CISS was used to assess obstructive membranes in CSF pathways compared with other sequences. Cine PC, follow-up imaging, and surgical findings were used to confirm obstructive membranes. RESULTS: Comparing the number of noncommunicating cases by using the conventional and 3D-CISS images, we found 26 new cases (19.4%) of 134 cases that were previously misdiagnosed as communicating hydrocephalus by conventional images. 3D-CISS sequence identified obstructive membranes invisible in other sequences, which facilitated selection of neuroendoscopy in the treatment of 31 patients (23.1%) in total who would have been otherwise treated with shunt insertion. These patients included 26 newly diagnosed noncommunicating cases after demonstration of intraventricular and/or fourth ventricular outlet membranes and 5 cases of communicating hydrocephalus with obstructing cisternal membranes. There were obstructions of the foramina of Luschka in 22 of 26 newly found noncommunicating cases. CONCLUSIONS: Conventional sequences are insensitive to obstructive membranes in CSF pathways, especially in the fourth ventricular exit foramina and the basal cisterns. 3D-CISS sequence, revealing these obstructive membranes, can alter patient treatment and prognosis.
Keywords: 3-DIMENSIONAL CONSTRUCTIVE INTERFERENCE; ENDOSCOPIC 3RD VENTRICULOSTOMY; OBSTRUCTIVE HYDROCEPHALUS; TECHNICAL NOTE; MEMBRANOUS OBSTRUCTION; OUTLET OBSTRUCTION; PEDIATRIC-PATIENTS; CRANIAL NERVES; CSF FLOW; 3D CISS